2020
DOI: 10.1037/xge0000705
|View full text |Cite
|
Sign up to set email alerts
|

Autistic adults anticipate and integrate meaning based on the speaker’s voice: Evidence from eye-tracking and event-related potentials.

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 97 publications
(196 reference statements)
0
22
0
Order By: Relevance
“…Four studies looked at predictions based primarily on social expectations, which are presumably learned over a lifetime of social experiences but may also have an innate component [Wynn, 2008]. All reported some type of impairment in making such predictions: Chambon et al [2017] and von der Lühe et al [2016] found that social cues induced weaker perceptual biases in action identification in the ASD group; Palumbo, Burnett, and Jellema [2015] found that biases in identification of emotions in changing faces were driven by pattern extrapolation rather than emotion‐related priors in the ASD group; and Barzy, Black, Williams, and Ferguson [2019] reported differences in eye movement (though not in EEG activity), indicating differences in predictions based on voice/topic associations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies looked at predictions based primarily on social expectations, which are presumably learned over a lifetime of social experiences but may also have an innate component [Wynn, 2008]. All reported some type of impairment in making such predictions: Chambon et al [2017] and von der Lühe et al [2016] found that social cues induced weaker perceptual biases in action identification in the ASD group; Palumbo, Burnett, and Jellema [2015] found that biases in identification of emotions in changing faces were driven by pattern extrapolation rather than emotion‐related priors in the ASD group; and Barzy, Black, Williams, and Ferguson [2019] reported differences in eye movement (though not in EEG activity), indicating differences in predictions based on voice/topic associations.…”
Section: Resultsmentioning
confidence: 99%
“…The RTs indicated their readiness for each specific stimulus and/or response, which indicated the extent to which they had predicted that stimulus and/or response. [Barzy et al, 2019; Deschrijver et al, 2016; Kunchulia et al, 2017, 2020; Lawson et al, 2017; Tam et al, 2017; Thillay et al, 2016].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hutchins & Brien, 2016;Nadig et al, 2010;Vabalas & Freeth, 2016) and our own previous work on pragmatic language comprehension in autistic adults (e.g. Barzy et al, 2020;Black et al, 2018Black et al, , 2019Ferguson et al, 2019). Post hoc calculations of power were conducted given the current sample size using the simr package in R (Green & MacLeod, 2016) and returned an estimated power of 87.9% with the significance level of α = .05 on 80% of occasions (as suggested by Cohen, 1988).…”
Section: Participantsmentioning
confidence: 99%
“…However, only a handful of studies have experimentally tested online emotional processing in narratives, or irony comprehension directly, among autistic adults. In contrast to the broader social‐communication impairments described above, these studies have largely demonstrated an undiminished ability to comprehend irony and track emotional states online, thus adding to a growing literature showing that autistic adults can integrate linguistic input with context in real‐time [e.g., Au‐Yeung et al, 2015; Barzy, Ferguson, Williams, & Black, in press; Black, Williams, & Ferguson, 2018; Ferguson, Black, & Williams, 2019; Howard, Liversedge, & Benson, 2017a, 2017b, 2017c]. Specifically, Au‐Yeung et al [2015] recorded eye movements while autistic and nonautistic participants read stories that could be interpreted as ironic or not, depending on the context.…”
Section: Introductionmentioning
confidence: 99%